Transition Metal‐Catalyzed Intermolecular Hydroarylation of Allenes. Issue 41 (14th September 2022) - Pagès, Lucas; Abed Ali Abdine, Racha; Monnier, Florian; Taillefer, Marc
Abstract: The intermolecular transition‐metal catalyzed hydroarylation of allenes has been widely explored since the early 1980s. This reaction allows the selective access to high‐value allylic or vinylic motifs through the formation of C−C bonds. In this frame, arenes (ArH), which are employed without any pre‐functionalisation, represent one of the most used families of aryl sources. Organoboronic derivatives (acids ArB(OH)2 and esters ArB(OR)2 ) constitute alternative, accessible and generally more reactive coupling partners, while aryl halides (ArX) are a third, less used type of aryl source. Whereas gold‐ and palladium‐based catalysts are often used with arenes and aryl boronic derivatives, respectively, as aryl sources, a wide range of other transition metals have also been employed. Experimental and theoretical studies have often been reported, thus affording mechanistic insights and allowing to suggest catalytic cycles. Abstract : Hydroarylation of allenes leads to the selective formation of highly valuable allylic or vinylic structures through C−C bond formation. In this frame, transition metal‐based catalysts have been broadly employed. This review highlights this topic, discussing advantages, limitations and mechanistic aspects of the related methods over the four last decades.